Staphylococcus sciuri outbreak at Tertiary Hospital in Benin - AHOYO, THEODORA ANGÈLE; YEHOUENOU AZEHOUN PAZOU, ELISABETH; BABA MOU, Lamine; Attolou Gbohoun, Aimé; BOCO, A.B.; DRAMANE, KARIM LAYE (My University, 2013)
Background: Infections due to Staphylococcus sciuri in hospitalized patients seem to be emerging in different countries. Their incidence and clinical impact with inpatients have not been studied in Benin. Objective: The aim of this study was to estimate the prevalence of Staphylococcus sciuri during bloodstream infection and to assess the importance of the hospital environment as a possible secondary reservoir of multiresistant bacteria capable of colonizing or infecting patients. Patients and methods: Between June and December 2008, clinical information and samples were collected from patients suspected to have nosocomial bloodstream infections at a tertiary hospital in Benin. The isolates were identified, tested for antimicrobial susceptibility. Particularly attention was paid to Staphylococcus sciuri and factors associated with the carriage. Concurrently, swabbing of environment was achieved. MALDI TOF of abundant proteins was applied to identify and to discriminate Staphylococcus sciuri isolates. Results: Nosocomial bactereamia incidence rate was 2, 58 cases per 1000 patient-days. The proportion of Staphylococcus sciuri among coagulase negative staphylococci was 24.5% and represented 15% of the environment specimens. Catheter was the commonest source of nosocomial bacteremia (41%). The frequency of resistance to methicillin for Staphylococcus aureus isolates was 36% and 44% for Staphylococcus sciuri isolates. Mass spectra were specific for five groups of S. sciuri isolates. Conclusion: Our survey revealed a high level of Staphylococcus sciuri among Coagulase Negative Staphylococcus isolated from blood specimen. There is a need to institute strict hospital infection control policy and a regular surveillance of resistance to antimicrobial agents.
Keywords: taphylococcus scuiri; Nosocomial bloodstream infection; Catheter